Association of Hyperuricemia With Immune Disorders and Intestinal Barrier Dysfunction - Lv, Qiulan; Xu, Daxing; Zhang, Xuezhi; Yang, Xiaomin; Zhao, Peng; Cui, Xuena; Liu, Xiu; Yang, Wan; Yang, Guanpin; Xing, Shichao (Frontiers in Physiology, 2020)
Background: More than 30-40% of uric acid was excreted via intestine, and the dysfunction of intestinal epithelium affect uric acid excretion. The involvement of gut microbiota in hyperuricemia has been evidenced, but the effects and mechanism of intestinal flora on intestinal immunity is lacking. Methods: We generated a Uox-knockout (Uox-/-) mouse using CRISPR/Cas9 technology for hyperuricemia model. We assessed lipometabolism by measuring changes of biochemical indicators. 4 kDa ﬂuorescein isothiocyanate (FITC)-labeled dextran was used to assess gut barrier function. 16S rRNA sequencing was performed to examine changes of gut microbial in human and mice fecal. RNA-sequencing, western blot, Q-PCR, ELISA and immunohistochemical analysis was used for measuring gene transcription, immune cells and cytokine in the intestine, serum, kidney, liver, pancreas and vessel. Results: We here identify that in both pre-clinical and clinical settings, inflammation related microbiota was increased in hyperuricemia group. Microbial pattern recognition associated Toll-like receptor pathway and inflammation associated TNF and NF-kappa B signaling pathway were significantly enriched. The increased inflammation related microbiota result in immune disorders and intestinal barrier dysfunction by upregulating TLR2/4/5 and promoting the release of IL-1β and TNF-α. Epithelial tight junction proteins occludin and claudin-1 was decreased. The pro-apoptotic gene Bax was increased. Circulatin LPS and TNF-α in systemic were increased in hyperuricemia mice. There was a positive correlation between the increase of intestine permeability and the increase of serum uric acid. Conclution: Hyperuricemia was characteristic with dysregulated intestinal immune and compromised intestinal barrier, which was accompanied by system inflammation. The results may be served as a basis for novel therapeutic interventions for hyperuricemia.